(Si(O2C6F4)2)14: self-assembly of a giant perfluorinated macrocyclic host by low-barrier Si−O bond metathesis - Hartmann, Deborah; Greb, Lutz (Angewandte Chemie. International edition, 2020)
The dynamic covalent self-assembly of 14 units of bis(perfluorocatecholato)silane leads to [Si(O2C6F4)2]14—the first giant perfluorinated macrocycle. The oligomerization process is monitored spectroscopically, and the macrocycle analyzed by single-crystal X-ray diffraction. The molecule forms a rigid cavity that can host two o-closo-dodecacarboranes. Computations rationalize the consistent and reproducible formation of the 14mer and disclose a non-catalyzed Si−O/ Si−O σ-bond metathesis with an exceptionally low energetic barrier. For the first time, the most prevalent linker in our geosphere-SiO4-is disposed to construct a shape-defined crystalline macromolecule.